Unveiling water resources of the Vietnamese Mekong Delta - Ghosh, Surajit; Rajakaruna, Punsisi; Tri, V. P. D.; Loi, N. T.; Trung, P. K.; Holmatov, Bunyod (International Water Management Institute (IWMI). CGIAR Initiative on Low-Emission Food Systems, 2023)
The Vietnamese Mekong Delta is responsible for half of the country’s rice production. This is possible due to abundant freshwater resources available for agriculture. This report provides a general overview of water resources in the region, presents unique water-related challenges using earth observation data, and description of measures to address them. Structurally, section one provides a general introduction followed by description of surface water resources, its uses and dynamics. Section three contains information on water infrastructure in the region. Section four covers water extent dynamics of small reservoirs followed by section five that focuses on groundwater pumping. Section six presents information about the Google Earth Engine – based tool developed to visualize surface waters and water infrastructure of the region for different time ranges using different satellites. Section seven focuses on institutional arrangements related to water management in the Vietnamese Mekong Delta. Finally, section eight provides concluding remarks and recommendations to overcome identified challenges.